问题 解答题
计算题:
(1)(-12)÷4×(-6)÷2
(2)(-
5
8
)×(-4)2-0.25×(-5)×(-4)3

(3)(-1
1
2
)-1
1
4
+(-2
1
2
)-(-3
3
4
)-(-1
1
4
)

(4)(-3)3÷2
1
4
×(-
2
3
)2+4-22×(-
1
3
)
答案

(1)(-12)÷4×(-6)÷2=(-12)×

1
4
×(-6)×
1
2
=9.

(2)(-

5
8
)×(-4)2-0.25×(-5)×(-4)3

=-

5
8
×16-0.25×(-4)×(-5)×(-4)2=-10-80=-90.

(3)(-1

1
2
)-1
1
4
+(-2
1
2
)-(-3
3
4
)-(-1
1
4
)

=-1

1
2
-1
1
4
-2
1
2
+3
3
4
+1
1
4

=(-1

1
4
+1
1
4
)+(-1
1
2
-2
1
2
)+3
3
4
=0-4+3
3
4
=-
1
4

(4)(-3)3÷2

1
4
×(-
2
3
)2+4-22×(-
1
3
)

=-27×

4
9
×
4
9
+4-4×(-
1
3
)

=-

16
3
+4+
4
3
=0.

选择题
问答题 案例分析题